Reducing Tobacco Use through Taxation in Trinidad and Tobago : Modelling the Long-term Health and Economic Impact - Marquez, Patricio V. (World Bank, Washington, DC, 2018)
This report uses selected scenarios for increasing excise taxes on tobacco products in Trinidad and Tobago, with the aim of reducing smoking prevalence across the population. These scenarios provide inputs for modeling the long-term health and cost benefits to the population of proposed excise tax increases. The report provides evidence from the modeling exercise. Impacts are calculated relative to the status quo before the tax hike and are modeled beginning in 2017 for 2025 and 2035. A microsimulation model was employed to simulate the long-term impact of tobacco taxations on the future burden of a range of NCDs. Specifically, the disease outcomes quantified were for coronary heart disease (CHD), stroke, chronic obstructive pulmonary disease (COPD), and lung cancer.